Desarrollo sostenible & economía circular: un estudio desde la responsabilidad social empresarial - Antúnez Sánchez, Alcides (2021)
The development model of the contemporary industrial society was established as a paradigm grounded on a depredatory urban industrial sector, based of the decadence of the rural society and nature, with a high social and ecological cost, with an increasing tendency to all humanity, and conditioned by neoliberalism, market system, foreign debts, underdevelopment, unequal trade, and the sequelae of a unipolar world in military political matters since the last century. The challenge imposed by the achievement of the sustainable development on the States in the 21st century will allow, among basic actions and tools, encouraging preventive environmental techniques in order to guarantee the right to a sound environment among third generation rights, which implies ensuring that environmental conditions will not deteriorate to the extent of affecting the living conditions of human beings where the environmental pollution has been increasing specially in the urban sector, which is evolving today with a new paradigm for the States through “circular economy”.